2018
DOI: 10.1016/j.pmedr.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic representation in lifestyle weight loss intervention studies in the United States: A systematic review

Abstract: Obesity remains a persistent public health and health disparity concern in the United States. Eliminating health disparities, particularly among racial/ethnic minority groups, is a major health priority in the US. The primary aim of this review was to evaluate representation of racial/ethnic sub-group members in behavioral weight loss interventions conducted among adults in the United States. The secondary aims were to assess recruitment and study design approaches to include racial/ethnic groups and the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 38 publications
(71 reference statements)
2
59
0
Order By: Relevance
“…Participants were mostly White females; however, the participant sample was much more diverse than many other previous behavioral nutrition/exercise interventions. In a recent systematic review of 94 weight loss interventions, African Americans comprised just 18% of samples, compared to 34% in the IMAGINE study [72]. In addition, the percentage of men in the IMAGINE study (22%) is similar to what has been found among 244 other previous lifestyle intervention studies (27%) [73].…”
Section: Strengths and Limitationssupporting
confidence: 59%
“…Participants were mostly White females; however, the participant sample was much more diverse than many other previous behavioral nutrition/exercise interventions. In a recent systematic review of 94 weight loss interventions, African Americans comprised just 18% of samples, compared to 34% in the IMAGINE study [72]. In addition, the percentage of men in the IMAGINE study (22%) is similar to what has been found among 244 other previous lifestyle intervention studies (27%) [73].…”
Section: Strengths and Limitationssupporting
confidence: 59%
“…However, most areas of research have groups that are underrepresented. Within the area of behavioral weight control, samples are predominately female [2][3][4][5] and non-Hispanic White [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly with younger age, non‐Caucasian ethnicity was also associated with higher expected disadvantages of PA. Previous research has suggested that while ethnic minorities are often underrepresented in lifestyle trials, this does not necessarily mean lower likelihood of completing (Haughton et al, 2018; Shrager, 2018). Our current results indicated that ethnicity was associated with attrition, but only during later stages of behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Women and those with a more affluent life situation tend to be overrepresented, even though men, ethnic minorities, as well as those from lower social‐economic background tend to have higher risk of developing, for example, T2D (Gavarkovs, Burke, & Petrella, 2016; Harreiter & Kautzky‐Willer, 2018; Siegel et al, 2018; Sortsø, Lauridsen, Emneus, Green, & Jensen, 2018). Similarly, higher lifestyle intervention attrition has been associated with sociodemographic and cognitive factors such as lower educational achievement, ethnicity, younger age, higher BMI, unemployment, and lower self‐efficacy (Burgess, Hassmén, & Pumpa, 2017; Goode et al, 2016; Haughton et al, 2018; Leung, Chan, Sea, & Woo, 2017).…”
Section: Introductionmentioning
confidence: 99%